The effectiveness of the ergonomic intervention program among foup handlers in Kulim, Kedah: intervention study / Nur Aisyah Azahari - Azahari, Nur Aisyah (2017)
Introduction: Most of the final process of Front Opening Unified Pod (FOUP) in semiconductor industries involved manual handling such as repetitive task, awkward posture and prolonged standing. The objective of this study was to assess the effectiveness of the ergonomic program among Front Opening Unified Pod (FOUP) handlers in Kulim, Kedah. Method: An intervention study was conducted on 25 FOUP handlers. Recruitment of the respondents was based on volunteer basis and stratified random sampling. The workers who have past health problem and part time job were excluded from this study. Modified Nordic Musculoskeletal Questionnaire (MNMQ) was distributed to the respondents and direct observation measurement was used to identify their postural angle. Rapid Entire Body Assessment (REBA) used to assess the risk of getting MSDs among the FOUP handlers. SPSS was used for statistical analysis via chi-square test and repeated measures ANOVA to indicate the association of MSDs before and after intervention. Result: The most MSDs prevalence among the workers in past seven days before the intervention implemented were neck (55%), shoulder (40%) and upper waist (33%). After three month intervention, the MSDs problem such as neck, shoulder and lower back of among FOUP handllers shows significant association with postural angle. Conclusion: Neck, ower back, wrist required special attention as their prevalence were higher compared to other body parts. The awkward body posture of bending contribute to these musculoskeletal problem. As a result, decrease the prevalence of MSDs among the FOUP handlers and upsurge the efficiency the production. I conclude that a longstanding ergonomic interference (two months) produces a statistically significant decrease in musculoskeletal disorders, yet not after only one month.